Indium segregation and In–Ga inter-diffusion effects on the photoluminescence measurements and nonlinear optical properties in lens-shaped InxGa1-xAs/GaAs quantum dots. (January 2022) - Choubani, M.; Maaref, H.; Saidi, F.
Abstract: In this work, we have theoretically investigated the indium segregation and In/Ga intermixing effects in lens-shaped Inx Ga1-x As/GaAs quantum dots coupled to their wetting layer. In the wetting layer, the segregation phenomenon is described by Muraki's et al. model. However, the radial and vertical indium distributions resulting from In/Ga intermixing effect in the quantum dot were taken into account assuming a three-dimensional Gaussian distribution. The results obtained via the Finite Difference Method clearly showed that the introduction of such effects is of a great importance to match the photoluminescence data. The obtained results also indicated that the indium segregation in the wetting layer and the inter-diffusion inside the quantum dots dramatically affected the linear, nonlinear and total absorption coefficients of the strained nanostructure under investigation. Besides, the obtained results showed that the total absorption coefficient achieved an optimum value with a red shift of the resonant energy upon increasing the pressure and a blue shift when increasing the temperature. Graphical abstract: Image 1 Highlights: Lens-shaped Inx Ga1-x As/GaAs quantum dot. Investigation of linear, nonlinear, and total absorption coefficients. Exploration of the indium segregation and In/Ga intermixing effects. Effects of wetting layer, pressure, temperature, and morphology. Comprehensive study conducted within framework of Finite Difference Method.